Advances in the study of the effects of gut microflora on microglia in Alzheimer’s disease - Wu, Jin-Jing; Wei, Zhe (Frontiers in Molecular Neuroscience, 2023)
Alzheimer’s disease (AD) is a central nervous system (CNS) degenerative disorder, is caused by various factors including β-amyloid toxicity, hyperphosphorylation of tau protein, oxidative stress, and others. The dysfunction of microglia has been associated with the onset and advancement of different neurodevelopmental and neurodegenerative disorders, such as AD. The gut of mammals harbors a vast and complex population of microorganisms, commonly referred to as the microbiota. There’s a growing recognition that these gut microbes are intrinsically intertwined with mammalian physiology. Through the circulation of metabolites, they establish metabolic symbiosis, enhance immune function, and establish communication with different remote cells, including those in the brain. The gut microbiome plays a crucial part in influencing the development and performance of microglia, as indicated by recent preclinical studies. Dysbiosis of the intestinal flora leads to alterations in the microglia transcriptome that regulate the interconversion of microglia subtypes. This conversation explores recent research that clarifies how gut bacteria, their byproducts, and harmful elements affect the activation and characteristics of microglia. This understanding opens doors to innovative microbial-based therapeutic strategies for early identification and treatment goals in AD.